Has India's Surrogacy Bill Failed Women Who Become Surrogates?. Issue 1 (June 2018) - Nair, Smitha Sasidharan; Kalarivayil, Rajesh
Surrogacy in India is a 2.5-billion-dollar industry. The article highlights how India's Surrogacy Bill, 2016, has failed the women who become surrogates. The bill constructs the image of a 'good woman' who is ready to bear the child of a relative as a 'good deed' for the perpetuation of the family name. It fails to address the fact that the woman consents to surrogacy under the unequal circumstances of poverty, casteism and the patriarchal exploitation of women within the family.